2017
DOI: 10.21315/mjms2017.24.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Protection by Ethanolic Extract from Ulva lactuca L. against Acute Myocardial Infarction: Antioxidant and Antiapoptotic Activities

Abstract: Background: Reactive oxygen species (ROS) play a major role in myocardial damage during acute myocardial infarction (AMI). This study aimed to determine the antioxidant and antiapoptotic activities of an ethanolic extract from Ulva lactuca L. (EEUL) against AMI.Methods: Thirty-six male Wistar rats were divided into six groups: one control group and five treatment groups. Treatment group II was given 85 mg/kg body weight (BW) of isoproterenol (ISO). Group III, IV and V were given ISO and EEUL at 250, 500 and 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(20 reference statements)
1
3
0
3
Order By: Relevance
“…Induction of apoptosis by DOX was also confirmed biochemically and immunohistochemically by increased DOI: 10.1159/000496109 caspase 3 activity and immunoreaction, respectively, in DOX-treated rats. Consistent with our data, several previous studies also reported a significant increase in caspase 3 activity and protein expression, and downregulation of antiapoptotic proteins following DOX exposure [Soni et al, 2011;El-Agamy et al, 2016;Widyaningsih et al, 2017]. Moreover, ROS initiated by DOX can cause Bax translocation to the outer mitochondrial membrane and subsequently leads to cytochrome C release from the mitochondria into the cardiomyocyte cytoplasm, which further activates caspase 3-dependent apoptosis [Darwish and Abd El Azime, 2013].…”
Section: Discussionsupporting
confidence: 90%
“…Induction of apoptosis by DOX was also confirmed biochemically and immunohistochemically by increased DOI: 10.1159/000496109 caspase 3 activity and immunoreaction, respectively, in DOX-treated rats. Consistent with our data, several previous studies also reported a significant increase in caspase 3 activity and protein expression, and downregulation of antiapoptotic proteins following DOX exposure [Soni et al, 2011;El-Agamy et al, 2016;Widyaningsih et al, 2017]. Moreover, ROS initiated by DOX can cause Bax translocation to the outer mitochondrial membrane and subsequently leads to cytochrome C release from the mitochondria into the cardiomyocyte cytoplasm, which further activates caspase 3-dependent apoptosis [Darwish and Abd El Azime, 2013].…”
Section: Discussionsupporting
confidence: 90%
“…In this regard, the MCF-7 cells were exposed to 250–1000 μg/mL of KLH for 24 h, and oxidative stress markers (GSH and LPO), ROS generation, MMP, and caspase enzyme activities were studied. ROS raised LPO level is known to decrease endogenous antioxidants such as glutathione (GSH) ( Widyaningsih et al, 2017 ). The elevated level of ROS has been reported to be involved in the cancer cell death ( NavaneethaKrishnan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cardioprotective nature of melatonin against ISO induced myocardial injury in rats has previously been shown [ 83 ], this new mechanism of dual protection afforded by melatonin to antioxidant enzymes, evident from the ITC pattern between ISO, melatonin and catalase, which shows that melatonin sequesters ISO molecules and prevents it from attacking the binding sites of catalase along with occupying and masking the active sites of catalase enzyme themselves thereby preventing any possibility of interaction between ISO and catalase is unique to this study and highlights the beneficial role of melatonin. Although many medicinal plants with antioxidant properties have been used as a cardioprotective agent against ISO [ 84 ], melatonin remains the most potent and promising candidate of all. The therapeutic role of exogenous melatonin in cardiovascular diseases has been discussed previously [ 85 ] suggesting it to be consumed through plant foods or by direct supplementation to promote various health benefits [ 86 ].…”
Section: Discussionmentioning
confidence: 99%